2018
DOI: 10.18805/lr-3848
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of resistance in chickpea varieties against Callosobruchus chinensis Linn. (Coleoptera: Bruchidae)

Abstract: Eleven chickpea varieties were screened for their biochemical resistance to the pulse beetle (Callosobruchus chinensis L.), a serious pest of the stored pulses. The varieties were found to arrest the growth and development of C. chinensis, at grub stages which were indicated by different parameters viz., oviposition, adult emergence, weight loss, developmental period and growth index. Among the various biochemical analyzed, high growth index was observed in the varieties PKG 2 (0.61), BG 1003 (0.62), BG 1053 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar finding was reported by Radha and Sushila (2014), Hosamani et al, (2018) and Jaiswal et al (2019). Development period in chick pea was in a range of 28± 0.35 days and this was almost in the range given by Swella and Mushobozy (2009) Kamble et al (2016) and Ahmad et al (2017). Maximum adult emergence was observed in green gram 120± 2 followed by cow pea and least in pea 60± 1, and those finding are in accordance with those of Deeba et al (2006) and Chandel and Bhaudaria (2015).…”
Section: Resultssupporting
confidence: 87%
“…Similar finding was reported by Radha and Sushila (2014), Hosamani et al, (2018) and Jaiswal et al (2019). Development period in chick pea was in a range of 28± 0.35 days and this was almost in the range given by Swella and Mushobozy (2009) Kamble et al (2016) and Ahmad et al (2017). Maximum adult emergence was observed in green gram 120± 2 followed by cow pea and least in pea 60± 1, and those finding are in accordance with those of Deeba et al (2006) and Chandel and Bhaudaria (2015).…”
Section: Resultssupporting
confidence: 87%
“…In our findings, increased developmental time was observed in desi chickpea followed by kabuli chickpea. Ahmad et al (2017) observed total developmental period (from egg-laying to adult formation) 28.67 days to 32.33 days on various chickpea varieties. Osman et al (2015) assessed the impacts of five temperatures on C. maculatus development on chickpea grains and stated that minimum total developmental time was 20.7 days (35 °C), followed by 23.8 days (30 °C), 27.7 days (28 °C), 38.3 days (25 °C) and 77.8 days (20 °C).…”
Section: Discussionmentioning
confidence: 89%
“…The lowest amounts of total flavonoids were recorded in ICPL 161 and ICPL 332 (0.40 and 0.36 mg/g respectively) (Table 1). Similarly, Ahmad et al, (2019) reported that flavonoids content of different chickpea varieties ranged from 0.283 to 0.466 mg/g. Rani et al, (2014) observed that flavonoids content in whole seed extract was (8.65±0.6 mg/g ) in pigeonpea.…”
Section: Total Flavonoids Contentmentioning
confidence: 95%